Micronutrients availability in a cleared forestland after seven years of continuous cultivation and eight years of natural fallow in an Alfisol, eastern Nigeria - Asadu, C.; Chibuike, G.; Dixon, A. (Progressive Science Publications, 2014)
Micronutrients content in a cleared forestland continuously cropped for seven years with cassava, maize, pigeon pea and their combinations and subsequently fallowed for eight years were monitored in this study in order to determine the availability of these nutrients after these years. Soil samples were collected at the end of the cultivation and fallow periods and were analysed for available zinc, copper, iron and boron in addition to available phosphorus, pH and organic matter. The results show that micronutrients content (except copper) in the various plots decreased after years of cultivation, these equally increased after the fallow period especially for available zinc. The rate of micronutrient recovery after fallow was more on the plots which had cassava as a treatment. Availability of micronutrients was affected by soil properties especially available phosphorus which had a significant (p < 0.05) negative correlation with zinc. Significant (p < 0.05) negative correlation between zinc and copper, as well as a significant (p < 0.01) positive correlation between boron and iron were obtained in this study. More research is needed in order to understand the interrelationships that exist among micronutrients in alfisol of eastern Nigeria.